Dictators, democrats, and development in Southeast Asia implications for the rest - Rock, Michael T. (New York, NY Oxford University Press, 2017)
Since 1960 only nine developing countries have succeeded in sustaining high growth. The aim of 'Dictators, Democrats and Development' is to examine how dictators and democrats in three of the nine, Indonesia, Malaysia and Thailand, who share broad similarities with the Rest, built and sustained pro-growth political coalitions.
Contents: Getting growth going is hard and rare -- History as prologue -- Dictators build and sustain pro-growth coalitions -- Dictators incite domestic capitalists to invest -- Selective interventions in rice agriculture -- The state and industrial development -- Technological upgrading -- Democrats, democratic developmental states and growth -- Democracy and corruption -- Lessons from IMT for the rest.
Previously issued in print: 2016.
Includes bibliographical references and index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Electronic books; Economic development -- Political aspects -- Indonesia; Economic development -- Political aspects -- Malaysia; Economic development -- Political aspects -- Thailand; Indonesia -- Economic policy; Malaysia -- Economic policy; Thailand -- Economic policy